Termination of Life on Request and Assisted Suicide - Beka Kebuladze (European Scientific Journal, ESJ, 2017)
The right to life in Georgia is guaranteed by the constitution which clearly states that everyone has the inviolable right to life and this right is protected by the law (6). In Georgian jurisdiction, euthanasia as the term is defined as follows: "Euthanasia - intentional termination of life on request of the patient who suffers from the terminal illness when the death is unavoidable” (7). The word "euthanasia" comes from the Greek words and means "good, easy death"(1). It consists of two parts - "eu" meaning "good" and "thanatos" meaning - "death". It means a deliberate hastening of a person's death or ending a life of the patient who is terminally ill and has incurable illness in order to relieve intractable suffering. Euthanasia is not a strange phenomenon in the modern world, though one can say that for certain categories of countries it really is. Society is diverse. Accordingly, each person has different opinion on different matters. It is logical that the diversity of opinions and plenty of controversies about the abovementioned issue is caused by its topical nature and scale. Topicality of the problem creates the base of searching preventive mechanisms of the ways of its solution. I would like to emphasize that it would be better to prevent the crime in advance, rather than thinking of a punishment after its commitment. A number of topical issues are discussed in sequence in the article, such as the modern scientific approach on the given issue, areas of the legislative base in Georgia and in the rest of the world, preventive measures, examples, discussion of the issue in the context of religion and what changes should be made in the field of crime prevention in Georgian preventive policy in the nearest future.